Meta‐analysis of the influence of lifestyle changes for preoperative weight loss on surgical outcomes. Issue 3 (17th October 2018) - Roman, M.; Monaghan, A.; Serraino, G. F.; Miller, D.; Pathak, S.; Lai, F.; Zaccardi, F.; Ghanchi, A.; Khunti, K.; Davies, M. J.; Murphy, G. J.
Abstract : Background: The aim was to investigate whether preoperative weight loss results in improved clinical outcomes in surgical patients with clinically significant obesity. Methods: This was a systematic review and aggregate data meta‐analysis of RCTs and cohort studies. PubMed, MEDLINE, Embase and CINAHL Plus databases were searched from inception to February 2018. Eligibility criteria were: studies assessing the effect of weight loss interventions (low‐energy diets with or without an exercise component) on clinical outcomes in patients undergoing any surgical procedure. Data on 30‐day or all‐cause in‐hospital mortality were extracted and synthesized in meta‐analyses. Postoperative thromboembolic complications, duration of surgery, infection and duration of hospital stay were also assessed. Results: A total of 6060 patients in four RCTs and 12 cohort studies, all from European and North American centres, were identified. Most were in the field of bariatric surgery and all had some methodological limitations. The pooled effect estimate suggested that preoperative weight loss programmes were effective, leading to significant weight reduction compared with controls: mean difference –7·42 (95 per cent c.i. –10·09 to –4·74) kg ( P < 0·001). Preoperative weight loss interventions were not associated with a reduction in perioperative mortality (odds ratio 1·41, 95 per cent c.i. 0·24 to 8·40; I 2 = 0 per cent, P = 0·66) but the event rate was low. The weight loss groups had shorter hospital stay (by 27 per cent). No differences were found for morbidity. Conclusion: This limited preoperative weight loss has advantages but may not alter the postoperative morbidity or mortality risk. Abstract : Possible, but how much is enough?